Comparison of Accrual Ratio and Cash Ratio Accuration in Financial Reports - Mahyudin Mahyudin; Sapto Hendri; Iman Waskito; M. Ali Fikri (IKIP Mataram, 2021)
Accounting and financial reporting fraud has been happening lately. Failure in estimating the veracity of financial reports starts from many aspects of accruals in the preparation of financial reports. This study seeks to explain the flow of financial transactions as important information, considering that activities in the financial sector require quick and relevant decisions. The flow of transactions in the financial reports consists of cash flows and accruals. Finance in business is almost similar to direct current and alternating current. In fact, this is misleading because of the ignorance of the readers of financial reports in interpreting profit, even though the misinterpretation will have an impact on investing errors. This study tries to analyze the results of financial ratio investments using the approach to the ratio of factors in the form of cash and accruals. Hermenuetics qualitative approach is used with data sourced from the Indonesia Stock Exchange. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange. Three forms of financial ratio analysis are used, namely the analysis of ROA (return of assets), ROI (return of investment), and ROE (return of equity). Researchers measure using a comparison of ROA, ROI, and ROE based on accruals and cash. The results of the comparison of the accuracy of the accrual ratio and the cash ratio in the financial reports are presented further in this article.